Association of Susceptibility Genes for Adolescent Idiopathic Scoliosis and Intervertebral Disc Degeneration With Adult Spinal Deformity. Issue 23 (1st December 2019) - Takeda, Kazuki; Kou, Ikuyo; Hosogane, Naobumi; Otomo, Nao; Yagi, Mitsuru; Kaneko, Shinjiro; Kono, Hitoshi; Ishikawa, Masayuki; Takahashi, Yohei; Ikegami, Takeshi; Nojiri, Kenya; Okada, Eijiro; et al.
Abstract : Study Design: Genetic case-control study of single nucleotide polymorphisms (SNPs). Objective: To examine the association of previously reported susceptibility genes for adolescent idiopathic scoliosis (AIS) and intervertebral disc (IVD) degeneration with adult spinal deformity (ASD). Summary of Background Data: ASD is a spinal deformity that develops and progresses with age. Its etiology is unclear. Several ASD susceptibility genes were recently reported using a candidate gene approach; however, the sample sizes were small and associations with ASD development were not determined. Methods: ASD was defined as structural scoliosis with a Cobb angle more than 15° on standing radiographs, taken of patients at age 40 to 75 years in this study. Subjects in whom scoliosis was diagnosed before age 20 were excluded. We recruited 356 Japanese ASD subjects and 3341 healthy controls for case-control association studies of previously reported SNPs. We genotyped four known AIS-associated SNPs (rs11190870 in LBX1, rs6570507 in GPR126, rs10738445 in BNC2, and rs6137473 in PAX1 ) and three IVD degeneration-associated SNPs (rs1245582 in CHST3, rs2073711 in CILP, and rs1676486 in COL11A1 ) by the Invader assay. Results: Among the AIS-associated SNPs, rs11190870 and rs6137473 showed strong and nominal associations with ASD ( P  = 1.44 × 10 −4, 1.00 × 10 −2, respectively). Of the IVD degeneration-associated SNPs, rs1245582 and rs2073711 showed no association with ASD, while rs1676486 showed a nominal association ( P  = 1.10 × 10 −2 ). In a subgroup analysis, rs11190870 was significantly associated with a Cobb angle more than 20° in the minor thoracic curve ( P  = 1.44 × 10 −4 ) and with a left convex lumbar curve ( P  = 6.70 × 10 −4 ), and nominally associated with an apical vertebra higher than L1 ( P  = 1.80 × 10 −2 ). Conclusion: rs11190870 in LBX1, a strong susceptibility SNP for AIS, may also be a susceptibility SNP for ASD. Thus, ASD and AIS may share a common genetic background. Level of Evidence: 4 Abstract : We investigated the genetic association between adult spinal deformity (ASD) and adolescent idiopathic scoliosis (AIS) or intervertebral disc (IVD) degeneration. A known AIS-associated single nucleotide polymorphism in LBX1 was clearly associated with ASD. Therefore, LBX1 may be a susceptibility gene for ASD.